Analisis Perbedaan Partisipasi Suami dan Tenaga Kesehatan terhadap Tingkat Kecemasan Ibu Intrapartum Primipara - Siti Khotimah; Evin Noviana Sari (Universitas STRADA Indonesia, 2018)
Childbirth is a fairly heavy period for mothers, where the birth process is like a mother's life and death stakes, especially in primiparous mothers, where they do not have the experience of giving birth. Psychological support and attention will have an impact on social life patterns of harmony, respect, sacrifice, compassion and empathy during the delivery process and from the technical aspects, can reduce aspects of resources such as: experts, normal delivery methods, acceleration, pain control and care neonatal. The presence of a companion childbirth is one of the moral support needed, because at this time the mother is experiencing severe stress.